Efforts To Increase Learning Outcomes Through Group Work Method In English Lessons - Nasution, Irmayanti Swastika (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Classroom action research generally aims to improve the quality of learning for students of class VIII SMP Negeri 3 Kisaran. specifically aims to: 1. Efforts To Increase Learning Outcomes Through Group Work Method In English Lessons For Class VIII Students SMP Negeri 3 Kisaran District Asahan academic year 2019/2020; 2. Describe the management of learning English by teachers; 3. Through Group Work Method. This classroom action research conducted in two cycles, each cycle consisting of planning, action, observation and reflection. Classroom action research conducted in class VIII SMP Negeri 3 Kisaran totaling 29 students. The subjects were English Lessons teacher class VIII and class VIII SMP Negeri 3 Kisaran, data were collected through observation, interviews, tests, and study documentation. The results of study in the first cycle reaches the average value of 77.87% after the first cycle and the second cycle, reflection and recommendation average value reached 86.49%.Ã‚Â Keywords: group work; learning outcomesÃ‚Â Ã‚Â Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran siswa kelas VIII SMP Negeri 3 Kisaran. secara khusus bertujuan untuk : 1. Upaya Peningkatan Hasil Belajar Melalui Metode Kerja Kelompok Dalam Pembelajaran Bahasa Inggris Pada Siswa Kelas VIII SMP Negeri 3 Kisaran kab. Asahan TP. 2019/2020; 2. Mendeskripsikan manajemen pembelajaran bahasa Inggris oleh guru; 3. Melalui Metode Kerja Kelompok. Penelitian tindakan kelas ini dilakukan dalam dua siklus, setiap siklus terdiri dari perencanaan, tindakan, observasi dan refleksi. Penelitian tindakan kelas dilakukan di kelas VIII SMP Negeri 3 Kisaran yang berjumlah 29 siswa. Subyek penelitian ini adalah guru mata pelajaran Bahasa Inggris kelas VIII dan kelas VIII SMP Negeri 3 Kisaran, data dikumpulkan melalui observasi, wawancara, tes, dan studi dokumentasi. Hasil belajar pada siklus I mencapai nilai rata-rata 77,87% setelah siklus I dan siklus II, nilai rata-rata refleksi dan rekomendasi mencapai 86,49%.Ã‚Â Kata Kunci: hasil belajar; kerja kelompok